[en] IMPLICATIONS OF PERSONAL CREDIT USE ON HOUSEHOLD BUDGET OF LOW INCOME CONSUMERS - LUIZA SICUPIRA MALBURG (MAXWELL, 2010)
[pt] O presente trabalho investiga a utilização do crédito concedido à população de baixa renda e o comportamento dos membros dessa população diante da necessidade de gerir endividamentos. O estudo se concentra na dificuldade - atestada pelo IBGE - desses consumidores chegarem ao final do mês com seus pagamentos em dia e com recursos para satisfazer as necessidades básicas de consumo. O estudo se desenvolve por meio de entrevistas qualitativas, com as quais explora a experiência e vivência do consumidor de baixa renda durante o processo de empréstimo e gerenciamento das dívidas. As entrevistas - gravadas e transcritas - produzem dados que são utilizados para identificar tanto os temas relacionados ao endividamento quanto a problemática associada aos consumidores tais como negociação de dívidas, acúmulo de dívidas, compulsividade na utilização de cartões de crédito, controle de gastos e outros mais. O estudo mostra que, apesar da oferta de crédito para a população de baixa renda vir sofrendo uma significativa expansão ao longo dos anos, ela causa transtornos para pessoas que utilizam o crédito sem planejamento rigoroso de seus gastos. Enquanto a maior oferta pode vir a desempenhar um papel estratégico no alívio da pobreza das classes menos favorecidas, a utilização do crédito ainda revela dificuldades decorrentes da manipulação, implícita ou explícita, por parte das instituições que operam nesse mercado. Além de outros resultados, o estudo salienta a necessidade de conscientização e esclarecimento em relação à utilização do crédito e a adoção de valores mais razoáveis tanto com relação aos juros referentes à quitação das dívidas quanto pelos objetivos para os quais os empréstimos são concedidos. === [en] This document is a survey on the use of credit available to low income class in Brazil, and about the behavior of these consumers in managing their debts. The study focus on the difficulty - confirmed by IBGE (the Brazilian Institute for Geography and Statistics) - this population has to get to the end of the month with their bills duly paid and still have enough resources to provide their basic needs. The study has been developed using qualitative interviews to explore the experience and the way the low income consumer faces the process, from borrowing money to the management of the debt. These interviews, recorded and transcript, produced data used to identify subjects related to indebtedness, accumulation of debt, compulsive use of credit cards, as well as the control of expenses and some others. The research shows that, in spite of the significant expansion on the offer of credit to the low income population along the years, it is a cause of trouble for people that use credit without planning carefully their expenses. While, on one hand, the larger offer of credit may play a strategic role in relieving the poverty effects in the less fortunate classes, on the other, using what could be a benefit remains difficult due to the manipulation practices that, explicit or implicitly, credit institutions operating in this sector commonly use to make business. Besides other outputs, the current study points out the need for the taker to be more conscious and to get clarification on the use of credit, but also on the adoption of more reasonable interest rates related to payment term, as well as on a careful previous analysis by the financial institution on the objectives for which the money is being lent.